Exposure to dairy manure leads to greater antibiotic resistance and increased mass-specific respiration in soil microbial communities. Issue 1851 (29th March 2017) - Wepking, Carl; Avera, Bethany; Badgley, Brian; Barrett, John E.; Franklin, Josh; Knowlton, Katharine F.; Ray, Partha P.; Smitherman, Crystal; Strickland, Michael S.
Abstract : Intensifying livestock production to meet the demands of a growing global population coincides with increases in both the administration of veterinary antibiotics and manure inputs to soils. These trends have the potential to increase antibiotic resistance in soil microbial communities. The effect of maintaining increased antibiotic resistance on soil microbial communities and the ecosystem processes they regulate is unknown. We compare soil microbial communities from paired reference and dairy manure-exposed sites across the USA. Given that manure exposure has been shown to elicit increased antibiotic resistance in soil microbial communities, we expect that manure-exposed sites will exhibit (i) compositionally different soil microbial communities, with shifts toward taxa known to exhibit resistance; (ii) greater abundance of antibiotic resistance genes; and (iii) corresponding maintenance of antibiotic resistance would lead to decreased microbial efficiency. We found that bacterial and fungal communities differed between reference and manure-exposed sites. Additionally, the β-lactam resistance gene ampC was 5.2-fold greater under manure exposure, potentially due to the use of cephalosporin antibiotics in dairy herds. Finally, ampC abundance was positively correlated with indicators of microbial stress, and microbial mass-specific respiration, which increased 2.1-fold under manure exposure. These findings demonstrate that the maintenance of antibiotic resistance associated with manure inputs alters soil microbial communities and ecosystem function.